MODERNIZING RELIGION AND CULTURE: SUTAN TAKDIR ALISJAHBANA’S PHILOSOPHICAL PERSPECTIVE OF VALUES - Jegalus, Nobertus (Universitas Islam Indonesia, 2020)
The mind is the most unique thing that differentiates a human being from an animal and it is through the mind as such humans improve their life quality. This is why modernizing religion and culture is indeed seen as a project of developing rationality which is one of six value groups in human beings’ lives. Rationality, in turn, gives birth to science, science technology, and finally, technology is used to develop humans’ economy and to support any advancement in various dimensions of human beings’ lives. For Islam, rationality is not something new because Islam is a rational religion. Rationality is, therefore, unique to Islam and it is not in contrast with Islam. In that sense, modernity as a major fruit of rationality is not against Islam. Learning from the West, that is, its science and technology, therefore, is necessary for Indonesia to be a modern nation, particularly in such fields as religion and culture.